The compilation of Qur’anic verses (juz 1 -15) and hadiths of Sahih Bukhari related to visual function - Yazid, Yazlin; Badarudin, Noor Ezailina; Mohamad, Hasbullah (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia., 2018)
The ability for us to see is actually due to the reflection of light that serves as a proof of the greatest creations of our Creator as stated in the Holy Quran, “Allah is the Light of the heavens and the Earth” (24:35). There are limited references specifically focusing on Revelations related to visual function. Thus, this study aims to provide a compilation of Quranic verses (Juz 1 to 15) and hadiths of Sahih Al-Bukhari related to visual function supported by scientifically proven facts. This may invite readers to reflect upon the wonders of creations by Allah mentioned in these Revelations that lead to the discovery of our modern science. A website named“Search Truth” on http://www.searchtruth.com/ was used as a tool to ease the finding of the Quranic verses and hadiths that are related to visual function by searching for the keywords “eye/eyes”, “see”, “light”, “sight” and “vision” in the search boxes provided in the website. The translations of Revelations containing those keywords were verified and related to visual function supported by scientifically proven facts from other reading materials. Twenty-eight Quranic verses and 57 hadiths of Sahih Al-Bukhari can be related to visual function supported by scientifically proven facts. Twelve Quranic verses that have the word “eye/eyes”, 7 verses with the word “light”, 2 verses with the word “see”, 6 verses with the word "sight” and 1 verse with the word “vision” can be related to visual function. As for hadiths, 49 hadiths have the word “eye/eyes”, 3 with the word “light”, 1 with the word “see”, 2 with the word “sight” and 2 with the word “vision” in their translations can also be related to visual function. Some of the Quranic verses and hadiths are related to anatomy, physiology and pathophysiology of the eyes, treatments for eye diseases, and other interesting findings.